Comparative education in the era of globalisation: evolution, mission and roles - Mark Bray (Universidad Nacional de Educación a Distancia (UNED), 2002)
To begin with this, we ought to say that Comparative Education is concerned with cross-national analysis and by its nature encourages its participants to be outward looking. The field of Comparative Education is shaped by globalisation. Held (1999:2) thinks that globalisation could be considered as «the widening, deeping and spending up of worldwide interconnectedness in all aspects of contemporary social life». Apart from that, we must say that there are some institutions, which promote this phenomenon called globalisation (among these institutions we can find the World Council of Comparative Education Societies -WCCES-). Globalisation has converted into an important topic for study. The comparative education's field possess some hyperglobalists who give reasons against that the world is transforming into borderless. Last but not least, we don't have to forget that by itself, comparative education is an interdisciplinary field; and because of that, the possibility of being developed for common conceptions is highly limited. Para empezar, deberíamos decir que la Educación Comparada está relacionada con el análisis transnacional y por su naturaleza alienta a sus partícipes a ser observadores externos.El campo de la Educación Comparada se encuentra modelado por la globalización.Held (1999:2) piensa que la globalización podría considerarse como «el ensanchamiento, profundización, y estabilización de interconexiones mundiales en todos los aspectosde la vida contemporánea social». Aparte de eso, debemos decir que existen algunas instituciones promotoras de este fenómeno llamado globalización (entre estas instituciones podemos hallar el Consejo Mundial de Sociedades de Educación Comparada). La globalización se ha convertido en un importante tema de estudio. El campo de educación comparada posee algunos hiperglobalistas, los cuales sostienen argumentos en contra de la transformación del mundo sin la existencia de fronteras.Por último, pero no por ello menos importante, no hemos de olvidar que por sí misma, la educación comparada es un campo interdisciplinar; y, debido a ello, la posibilidad de desarrollar conceptos comunes es muy limitada.